The Search for the Perfect Indicator : Reflections on Monitoring and Evaluation of Resilience for Improved Climate Risk Management - Hallegatte, Stephane; Engle, Nathan L. (Elsevier, 2019)
Resilience-building activities are increasingly evident in development projects, and as a result, there is a growing focus on monitoring and evaluating the associated outcomes of these projects for improved climate risk management. Significant challenges in measuring resilience, however, contribute to both a tendency towards imperfect quantified metrics, and a quest for universal resilience indicators that can be aggregated across projects, institutions, and geographies. In this paper, we draw from lessons across various sectors typically outside of the traditional resilience and climate risk management realm to highlight potential pitfalls and unintended consequences of such metrics. We then discuss several “thought experiments” to identify the desired characteristics development practitioners would want projects to demonstrate, but for which there exist risks for imperfect aggregated indicators to create perverse incentives. Process-based metrics that focus on the quality of a project’s design and implementation are more likely to avoid these pitfalls and should be considered a viable alternative to aggregated universal resilience indicators.